Influence of Pre-Training Predator Stress on the Expression of c-fos mRNA in the Hippocampus, Amygdala, and Striatum Following Long-Term Spatial Memory Retrieval - VanElzakker, Michael B.; Zoladz, Phillip R.; Thompson, Vanessa M.; Park, Collin R.; Halonen, Joshua D.; Spencer, Robert L.; Diamond, David M. (Frontiers in Behavioral Neuroscience, 2011)
We have studied the influence of pre-training psychological stress on the expression of c-fos mRNA following long-term spatial memory retrieval. Rats were trained to learn the location of a hidden escape platform in the radial-arm water maze, and then their memory for the platform location was assessed 24 h later. Rat brains were extracted 30 min after the 24-h memory test trial for analysis of c-fos mRNA. Four groups were tested: (1) Rats given standard training (Standard); (2) Rats given cat exposure (Predator Stress) 30 min prior to training (Pre-Training Stress); (3) Rats given water exposure only (Water Yoked); and (4) Rats given no water exposure (Home Cage). The Standard trained group exhibited excellent 24 h memory which was accompanied by increased c-fos mRNA in the dorsal hippocampus and basolateral amygdala (BLA). The Water Yoked group exhibited no increase in c-fos mRNA in any brain region. Rats in the Pre-Training Stress group were classified into two subgroups: good and bad memory performers. Neither of the two Pre-Training Stress subgroups exhibited a significant change in c-fos mRNA expression in the dorsal hippocampus or BLA. Instead, stressed rats with good memory exhibited significantly greater c-fos mRNA expression in the dorsolateral striatum (DLS) compared to stressed rats with bad memory. This finding suggests that stressed rats with good memory used their DLS to generate a non-spatial (cue-based) strategy to learn and subsequently retrieve the memory of the platform location. Collectively, these findings provide evidence at a molecular level for the involvement of the hippocampus and BLA in the retrieval of spatial memory and contribute novel observations on the influence of pre-training stress in activating the DLS in response to long-term memory retrieval.